2006
DOI: 10.1007/s10725-006-9103-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydro- and osmopriming of chickpea (Cicer arietinum L.) seeds on enzymes of sucrose and nitrogen metabolism in nodules

Abstract: Three year data on the effect of waterand mannitol (4%) priming of chickpea seeds (12 h at 25°C) showed higher number and biomass of nodules in the plants from primed seeds than from non-primed seeds. The biomass of nodules increased to 75 DAS but decreased by 90 DAS. Activities of sucrose metabolism enzymes (sucrose synthase (SS) and alkaline invertase) and of nitrogen metabolism (glutamine synthetase (GS), glutamate synthase (GOGAT) and glutamate dehydrogenase (GDH)) in nodules of primed and non-primed crops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 22 publications
7
24
0
Order By: Relevance
“…However, in the case of seed priming, the e ect continues longer (Bruce et al 2007). It has been reported that elevated sucrose synthase and glutamate synthase activities were observed in the seed-primed nodule of the chickpea, and these elevated activities might be responsible for increasing the nodule biomass and metabolic activity, thereby increasing seed ll (Kaur et al 2006). us, the acquired tolerance to abiotic and biotic stress observed in the present study suggests that the e ect of the seed-priming treatment continues longer and is more e ective than the plant-priming treatment.…”
Section: Discussionsupporting
confidence: 54%
“…However, in the case of seed priming, the e ect continues longer (Bruce et al 2007). It has been reported that elevated sucrose synthase and glutamate synthase activities were observed in the seed-primed nodule of the chickpea, and these elevated activities might be responsible for increasing the nodule biomass and metabolic activity, thereby increasing seed ll (Kaur et al 2006). us, the acquired tolerance to abiotic and biotic stress observed in the present study suggests that the e ect of the seed-priming treatment continues longer and is more e ective than the plant-priming treatment.…”
Section: Discussionsupporting
confidence: 54%
“…Seed priming strategy has been widely used to resolve the storage problem by improving the seed vigour, and is successful in many crops, ornamental plants, and forages (Heydecker et al 1973;Rush 1991;Finch-Savage et al 2004;Kaur et al 2006). in priming, seeds are exposed to restricted water availability under controlled conditions which allows some of the physiological processes of germination to occur and then, before germination is completed, the seeds are usually redried for short-term storage before sowing (Wright et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The irst technique consists in exposing the seeds to a limited quantity of water in a continuous or successive manner at a suitable temperature. This is an inexpensive technique often used for ield-grown cereals and legumes to accelerate germination [81]. The second technique consists in treating the seeds with microbiological agents such as rhizobia, Azospirillum, Pseudomonas, Bacillus, Trichoderma, Gliocladium and other species and aims to improve the vigour and viability of the seeds.…”
Section: Other Techniques Of Seed Primingmentioning
confidence: 99%
“…It has been shown that it can improve nodulation, N 2 capacity in legumes and nutrient acquisition, especially in less fertile soils [81]. Studies have reported that plants from treated seeds have shown high capacity to form nodules and accumulate large amounts of N, K + and P, especially under stress conditions [93,94].…”
Section: Osmopriming and N 2 -Ixing Symbiosismentioning
confidence: 99%